JURIDICAL REVIEW OF PRENUPTIAL AGREEMENTS - Royani, Esti; Nortjahjo, Arief; Sobirov, Bobur; Triana, Astri (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
A prenuptial agreement or commonly referred to as a prenuptial agreement is a contract or agreement that is equally agreed upon by a married couple, either before the marriage takes place, or during the marriage bond. In conducting research to be more focused, the author made a formulation of the problem, namely how is the legal provisions of the prenuptial agreement based on Law Number 16 of 2019, how is Amendments to Law Number 1 of 1974 concerning Marriage in Indonesia and the Legal Effects on Marital Property with the Prenuptial Agreement in Indonesia. The type of research used in this writing is normative legal research. Normative research is carried out by collecting data and information about the legal norms you want to research, then analyzing the data and information to get a deeper understanding of existing legal norms. Normative research methods can be carried out by means of literature studies, namely by collecting library materials or legal sources relevant to the research topic. The results showed that the forms of this marriage agreement include marriage agreements with togetherness of profit and loss, marriage agreements with togetherness of results and elimination of togetherness of wealth. The content of the agreement must be discussed carefully. You must ensure that you and your partner agree on the content of the agreement and are consistent with your values. For example, how joint property will be managed and divided if one day you divorce.